THE PROBLEM OF OBJECTIVE AND AXIOLOGICAL NORMS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The study of the question of the linguistic norm, the literary norm in the scientific and theoretical aspect is currently just beginning in Kyrgyz linguistics. The article examines the objectivity of the linguistic norm and its evaluative nature, with a brief discussion of whether the norm is a multifaceted phenomenon peculiar not only to literary language and its various forms, but also to natural language as a whole.
Keywords: national epoch, literary language, linguistic norm, Kyrgyz language, Kyrgyz linguis- tics, dialect